Dampak Diversifikasi Ekspor Terhadap Pertumbuhan Ekonomi Negara-Negara Anggota ASEAN - Faizal Amir; Dedi Budiman Hakim; Tanti Novianti (IPB University, 2018)
This study aims to analyze the impact of diversification of exports on economic growth in the ASEAN. The sample used in this study is the eight member countries of ASEAN for the period 2006-2014. The dependent variable is the growth of income per capita, while the independent variable which is based on the theory of Solow growth include number of workers, total of investment and export diversification index. The Observations are estimated using pooled least square. Based on these results, the majority of ASEAN countries have positive relation between export diversification index and the growth of income per capita. At times of crisis, the export diversification index in the ASEAN is no longer a positive impact on national income which is shown by the negative coefficient on the dummy variable interaction between the global crisis of 2008 with an export diversification index.